Sistem Pemilihan Keputusan memilih Handphone Dengan Menggunakan Metode Simple Addictive Weighting Berbasis Web - Prasetyo, Hendrik Dwi; Setiabudi, Djoni Haryadi; Setiawan, Alexander (Jurnal Infra, 2018)
Handphone or Mobile phone by most people as a mobile phone is the most commonly used communication tool in everyday life. The price offered varies depending on the condition of the phone. Mobile phone can be used without wired network.In the development of this very rapid information system, it is not difficult to solve such problems. One of them with decision-making system. Decision-making system is one way to achieve a certain goal to be achieved. Decision-making system can be done through the process of data collection, and with consideration of determining the decision. In determining this decision required a method to overcome the problem, namely by using the method of Simple Additive Weighting (SAW).Based on the results of bakers, 60% of respondents rated well in appraisal of apps, 40% of respondents rated very well in assessing the ease of use of the application, 50% of respondents rated good in assessing the completeness of information, 50% of respondents rated good in assessing conformity in needs, 40% respondents rate good in assessing the resulting report, 50% of respondents rate good in assessing the overall application.